UMPSA and YASA launch Akademi Menara Gading 2.0 - Naqiah, Puaad (UMPSA, 2024)
GAMBANG, 2 October 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA), in partnership with its strategic collaborator, Yayasan Al-Sultan Abdullah (YASA), launched the Akademi Menara Gading 2.0 programme today at Dewan Astaka, UMPSA Gambang Campus.